2006
DOI: 10.1242/jeb.02237
|View full text |Cite
|
Sign up to set email alerts
|

The role of adrenergic stimulation in maintaining maximum cardiac performance in rainbow trout (Oncorhynchus mykiss) during hypoxia,hyperkalemia and acidosis at 10°C

Abstract: SUMMARY As rainbow trout approach exhaustion during prolonged exercise, they maintain maximum cardiac output despite the fact their venous blood, which bathes the heart, becomes hypoxic, acidotic and hyperkalemic. Because these factors are individually recognized to have detrimental inotropic and chronotropic effects on cardiac performance, we hypothesized that adrenergic stimulation is critical in maintaining maximum cardiac performance under these collectively adverse conditions in vivo. To te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 59 publications
1
66
2
Order By: Relevance
“…An increase in Pco 2 to 8 kPa reduced Q max and PO max to a degree similar to that observed at 6 kPa but also resulted in arrhythmia without recovery in subsequent normocapnia. These data imply that cardiac damage, or at the very least temporary myocardial dysfunction (e.g., Hanson et al 2006), occurs at 8-kPa co 2 , a level of hypercarbia known to induce morbidity in vivo (D. W. Baker and C. J. Brauner, unpublished observations). ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…An increase in Pco 2 to 8 kPa reduced Q max and PO max to a degree similar to that observed at 6 kPa but also resulted in arrhythmia without recovery in subsequent normocapnia. These data imply that cardiac damage, or at the very least temporary myocardial dysfunction (e.g., Hanson et al 2006), occurs at 8-kPa co 2 , a level of hypercarbia known to induce morbidity in vivo (D. W. Baker and C. J. Brauner, unpublished observations). ).…”
Section: Discussionmentioning
confidence: 81%
“…Maximum cardiac performance of white sturgeon heart has not been previously assessed in situ, but it would be expected to be lower than that of a pelagic predator such as rainbow trout. Relative to those of rainbow trout, white sturgeon hearts exhibited a 50% lower intrinsic f H (at 10ЊC; Arthur et al 1992;Hanson et al 2006), a 20%-40% lower Q max (Hanson et al 2006), and a 75% lower PO max (Hanson et al 2006). The lower power output of white sturgeon hearts (∼1.2-1.5 mW g ventricle Ϫ1 ) may reflect their limited athletic prowess.…”
Section: Maximum Cardiac Performance During Hypercapniamentioning
confidence: 92%
See 1 more Smart Citation
“…Specifically, data on 10°C-acclimated Atlantic cod (Axelsson, 1988) suggest that adrenaline is not required for basal or maximum cardiac performance, whereas studies on several teleosts show that adrenergic sensitivity is a critical compensatory mechanism that enables the fish myocardium to maintain contractility during acute cold exposure (e.g. Franklin and Davie, 1992;Keen et al, 1993;Aho and Vornanen, 2001;Shiels et al, 2003;Galli et al, 2009), hypoxia and alterations in blood chemistry that are associated with intense exercise (Hanson et al, 2006). However, the apparent lack of myocardial responsiveness to adrenaline in cod may be due to the fact that only a single experimental temperature (10°C) has been examined to date.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have shown that certain important organs, including the brain [21,35] and cardiorespiratory system [18,19,36], have a contingent mechanism to combat hypoxia. However, these strategies did not seem to apply to the ocular system, which might predispose the eyes to developmental damage upon hypoxia.…”
Section: Discussionmentioning
confidence: 99%